CALCULATION AND COMPARATIVE ANALYSIS OF SOME EXHAUST GASES EMISSIONS DURING USE TRADYTSIYNH AND ALTERNATIVE AVIAION FUEL - Бойченко, С. В.; Яковлєва, А. В.; Наумчук, Г. О (Science-based technologies, 2015)
This article is devoted to investigation of the environmental problems associated with the use of fuels for air-jet engines. Energy resources that are available nowadays and may be used for production of fuels for air-jet engines similarly to crude oil are described. The main components of the exhaust emissions of gases that result from the use of traditional and alternative aviation fuels are considered and analyzed. Particular attention is paid to assessment of the negative impact of the use of petroleum fuels for air-jet engines on the current state of the environment. The possibility of reducing emissions of certain exhaust gases from aircrafts using aviation biofuels is shown at the example of fuels obtained from vegetable oil-containing feedstock. The paper indicated the potential positive effect of the use of biofuels for aviation.